Factors Attracted New Businesses Towards Jaffna District - A Study on Post War Perspectives - Archchutha, T.; Kumaradeepan, V.; Karunanithy, M. (University of Jaffna, 2014)
ervices. Most of the areas of the Jaffna district have not been observed by the companies last few decades due to the political obstacles in those areas. There is very huge potentials exist in several areas of Jaffna district, though it was not capitalized by the companies. Since end of the civil war in 2009 Post war recovery reform of the commercial system has been pivotal in accelerating economic growth. Several factors cause the companies move towards new market. Hence it is clear that the companies’ entrance to Jaffna district is booming. It is worthwhile to identify the factors which attracted the companies towards Jaffna. The objective of this study is to find out the most influencing factors of the companies for moving towards markets of Jaffna district. This study found out which factors influenced highly in attracting the companies towards Jaffna among several reasons such as infrastructure, brand awareness, buying behavior of the people, income level and literacy level, CSR Implementation, distribution channel, promotional strategies. Primary data were collected from companies through questionnaire. The sample was 60 companies which moved to Jaffna after conclusion of civil war 2009. Collected data has been analyzed by using quantitative method to find out the most influencing factor of movement. Seven factors have been operationalized by using 14 measures.
Keywords: New Market Movement; Postwar Perspective; Factor Analysis